PROSES PENYIDIKAN DAN PENUNTUTAN TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK DIWILAYAH KABUPATEN SEMARANG - Setyo Hartanto; Sri Endah Wahyuningsih (UNISSULA Semarang, 2018)
On the process of investigation and prosecution of criminal acts of theft committed by children in the region of Semarang Regency there are differences in the implementation of handling of child cases in accordance with the criminal justice system and there are obstacles and solutions that must be faced by investigators and public prosecutors with the enactment of Law No. RI. 11 of 2012.This study the author uses the method of Empirical Juridical approach is the way or procedure used to solve research problems by researching secondary data first to then proceed with researching the primary data that exist in the field. By collecting primary data that is data obtained directly from the community or field and secondary data is data obtained through literature materials.The child's handling process begins with the investigator receiving the child's case from the report, the complaint and the possibility of the investigator knowing himself then along with Bapas, the victim's side and the parent's side of the perpetrator and the other related relation whether to be forwarded or diverted. If there is a verdict and it is successful, it is requested by the local court to obtain legal force, but if the diversion is unsuccessful then the case file proceeds to the Investigation process after the case file is deemed complete and complete, then according to the law of the case submission is valid and complete, public without the need for more processing. The transfer of juridical responsibilities to the dossier, legal liability for a child suspect and legal liability for any evidence or item seized.Furthermore, after the public prosecutor receives the file from the investigator, if eligible to do the diversionary effort then must perform a diversionary effort, if not achieved then the prosecutor proceeded to check the completeness of the case both formally and materially to know more clearly whether the case can proceed to prosecution process or not and with complete evidence in order to be transferred to the court for continued trial by applying a criminal procedural law using a restorative justice approach. Against these obstacles and solutions both investigators and public prosecutors make their own efforts by approaching internally and externally from each agency.Keywords: Child Criminal Justice System, Child Investigator, Child Prosecutor,Diversi, Restoration Justice